1985
DOI: 10.1530/jrf.0.0740419
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of LH, oestradiol-17  and progesterone in the peripheral plasma of swamp buffalo COWS (Bubalus bubalis) around the time of oestrus

Abstract: Peripheral plasma concentrations of LH, oestradiol-17\g=b\ and progesterone were measured in 13 mature swamp buffalo cows at 4-h intervals from 36\p=n-\40h before until 36\p=n-\40h after the onset of oestrus. Mean LH concentrations increased sharply to a peak of 35 ng/ml and returned to basal levels of 5 ng/ml within a 12-h period beginning soon after the onset of oestrus. Mean oestradiol-17\g=b\ concentrations were within the range 9\p=n-\13pg/ml from 36\p=n-\40h before until 12\p=n-\16h after the onset of oe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2
1

Year Published

1986
1986
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
3
17
2
1
Order By: Relevance
“…Mean plasma LH levels reported in this study were lower those reported by Janakiraman et al (1980) and of same order as those reported by Avenell et al (1985), while the progesterone levels were higher than those reported by Jainudin et al (1983) in swamp buffalo. Pulses of LH always occurred concomitantly with pulses of FSH suggesting that in buffaloes gonadotrophin releasing hormone (GnRH) is also the sole hypothalamic releasing hormone for both LH and FSH as reported earlier in cows (Convey 1973).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Mean plasma LH levels reported in this study were lower those reported by Janakiraman et al (1980) and of same order as those reported by Avenell et al (1985), while the progesterone levels were higher than those reported by Jainudin et al (1983) in swamp buffalo. Pulses of LH always occurred concomitantly with pulses of FSH suggesting that in buffaloes gonadotrophin releasing hormone (GnRH) is also the sole hypothalamic releasing hormone for both LH and FSH as reported earlier in cows (Convey 1973).…”
Section: Discussionsupporting
confidence: 70%
“…Changes in the pituitary and ovarian hormones during the periovulatory phase of the oestrous cycle of the cow (Schams et al 1977;Dobson 1978) and of the buffalo (Janakiraman et al 1980;Jainudin et al 1983;Avenell et al 1985) have been described. The pulsatile secretion pattern of gonadotrophin and ovarian steroids during this period has been described in cows .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Murrah buffaloes have higher overall plasma oestradiol concentrations than do swamp buffaloes and cows. Values in the luteal phase of 10-15 pg/ml, and at oestrus of 31-34 ± 1-70 pg/ml, in Murrah buffaloes (Batra & Pandey, 1982) compare with the lower values of 2-9pg/ml and 90-130pg/ml respectively for swamp buffaloes (Kanai & Shimizu, 1984;Avenell, Saepudin & Fletcher, 1985), and 1-6 pg/ml and 10-15 pg/ml respectively in cows (Dobson & Dean, 1974;Glencross & Pope, 1981 (Batra & Pandey, 1982) compared to lower values of 15 pg/ml and 36 pg/ml at respective stages in cows (Pandey, Pahwa, Suri & Batra, 1981). This may reflect the higher fat content of buffalo milk (Kay, 1974) as 65% of milk oestradiol is located in the lipid phase (Wolford & Argoudelis, 1970) and analyses on defatted cow milk have revealed very similar concentrations to those in plasma (Glencross & Abeywardene, 1983).…”
Section: Pubertymentioning
confidence: 62%
“…Enucleation of the corpus luteum, or prostaglandin analogue administration before Day 12 of the cycle, does not result in PGFM release (Kindahl, Lindell & Edqvist, 1980 (Thatcher et al, 1984). No Razdan & Galhotra, 1980;Arora & Pandey, 1982a; Kanai & Shimizu, 1984;Avenell et al, 1985). Similar values were obtained for zebu by Carr (1972), and for cows by Snook, Saatman, & Hansel (1971); Schams, Schallenberger, Hoffman & Karg (1977) and Dobson (1978a).…”
Section: Pubertymentioning
confidence: 64%
See 1 more Smart Citation